Conditioning for dance. - Franklin, Eric, ....- (Champaign : Human Kinetics, 2004)
Even the best sense of rhythm, the most careful technical training, and the most astute dance intuition aren't enough to make a dancer truly excel; you also need focused strength, balance, and flexibility to execute the movements with power and grace. Conditioning for Dance improves your technique and performance in all dance forms by strengthening the body's core (abdominal and back muscles) while improving coordination, balance, and alignment and optimizing flexibility. The result is more lift without tension, deeper plis, higher jumps with less effort, tighter turns, and improved extension and turnout. Conditioning for Dance is the result of years of practical experience combined with scientific and anatomical analysis. Author Eric Franklin is an internationally known dancer, teacher, choreographer, and writer. His innovative, proven techniques will help you execute key dance skills better as you * strengthen the muscles you use in dance by performing exercises with elastic resistance
Bands; * start and move in proper alignment using imagery; * improve your balance and release tension through playful exercises with small balls; * develop leg and torso power that translates to higher jumps and tighter turns; * and optimize your flexibility through touch, movement awareness, and imagery. The book features 102 imagery illustrations paired with dance-specific exercises to help you maximize body-mind conditioning and develop more fluid mobility, balance, and tension release. The book culminates with a 20-minute, full-body workout routine designed to help dancers warm up, condition, and refine their dance technique. You'll learn how to execute lifelong dance skills that give power without the risk of injuries. By working the muscles through movements and ranges of motion that approximate the demands of your chosen dance form, you directly enrich your performance capabilities. And as you strengthen the body's core, stretch to gain just the right amount of flexibility
And incorporate the power of the mind, you unleash your full artistic and physical potential
Inhoudsopgave : Chapter 1. Mind-Body Conditioning Chapter 2. Embodied Imagery Chapter 3. Reflexive Balance Chapter 4. Relaxed Flexibility Chapter 5. Aligned Movement for Improved Technique Chapter 6. Strengthening the Center Chapter 7. Building Power in the Legs and Feet Chapter 8. Developing Power in the Torso and Arms Chapter 9. Improving Turns, Jumps, and Turn-Out Chapter 10. Thera-Band Centre Workout
Ondertitel op omslag: Training for peak performance in all dance forms.
Keywords: Dansen -- Fysiologie; Fitness